1997
DOI: 10.1074/jbc.272.6.3739
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Classes of Sulfhydryls Modulate the Skeletal Muscle Ca2+ Release Channel

Abstract: Two sulfhydryl reagents, N-ethylmaleimide (NEM), an alkylating agent, and diamide, an oxidizing agent, were examined for effects on the skeletal muscle Ca 2؉ release channel. NEM incubated with the channel for increasing periods of time displays three distinct phases in its functional effects on the channel reconstituted into planar lipid bilayers; first it inhibits, then it activates, and finally it again inhibits channel activity. NEM also shows a three-phase effect on the binding of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
100
0
1

Year Published

1997
1997
2016
2016

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 87 publications
(106 citation statements)
references
References 35 publications
5
100
0
1
Order By: Relevance
“…To understand the role of thiols in redox-signaling events related to cell survival/apoptosis, we have studied the effect of thiol alkylation on activation of Akt by PDGF-BB in VSMC. NEM has been used extensively as a specific thiol-alkylating agent (36,37). To determine thiol alkylation by NEM, growth-arrested VSMC were treated with and without 20 M NEM for 30 min, and free thiols were measured using 5,5Ј-dithiobis(2-dinitrobenzoic acid) reagent (35).…”
Section: Resultsmentioning
confidence: 99%
“…To understand the role of thiols in redox-signaling events related to cell survival/apoptosis, we have studied the effect of thiol alkylation on activation of Akt by PDGF-BB in VSMC. NEM has been used extensively as a specific thiol-alkylating agent (36,37). To determine thiol alkylation by NEM, growth-arrested VSMC were treated with and without 20 M NEM for 30 min, and free thiols were measured using 5,5Ј-dithiobis(2-dinitrobenzoic acid) reagent (35).…”
Section: Resultsmentioning
confidence: 99%
“…The intrinsic Zn# + might be essential for function of RyRs. It has been shown that RyR1s can be modulated by multiple classes of thiol groups [18]. Thus, as another mechanism, Zn# + might have its effect through binding to thiol groups on RyR1s.…”
Section: Interaction Of the Effects Of Zn 2 + And Other Ryr Modulatorsmentioning
confidence: 99%
“…The identification of the cysteines involved in these modulations is difficult because RYR1 has 100 cysteines per subunit. However, the functionally important cysteines appear to be hyper-reactive (21)(22)(23). We have previously shown that the N terminus of RYR1 contains sulfhydryls that react rapidly with NEM (19).…”
Section: Cam Protects Both Cysteines Required For Oxidation-inducedmentioning
confidence: 99%